A Chiron Approach to the Stereoselective Total Synthesis of Phomonol and Phytotoxic Nonenolides. Issue 44 (10th February 2020) - Chandra, Naveen; Fernandes, Rodney A.
Abstract : A common strategy from d ‐glucono‐δ‐lactone to the pyran natural product phomonol and the phytotoxic nonenolides has been developed. The key steps include a one‐pot conversion of d ‐glucono‐δ‐lactone to β‐hydroxy‐γ‐vinyl‐γ‐lactone and diastereoselective Grignard reaction. The synthesis of phomonol also involved cross‐metathesis and intramolecular oxa‐Micheal addition, while that of nonenolides was based on Yamaguchi esterification and intramolecular ring‐closing metathesis (RCM). Abstract : A common strategy from d ‐glucono‐δ‐lactone to the pyran natural product phomonol and the phytotoxic nonenolides has been developed based on diastereoselective Grignard reaction and metathesis as key steps